2020
DOI: 10.1111/jfbc.13512
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the co‐exposure of melanoma cells to chlorogenic acid and a moderate‐strength static magnetic field

Abstract: One of the most malignant skin cancers is melanoma-it has a high metastatic potential as well as a high resistance to treatment, which results in a high mortality rate. The basic method for treating early-stage melanomas is surgery alone. If surgery is not possible or as an adjuvant therapy, radiotherapy is used; chemotherapy is rarely used because of its low response rate (Perera et al., 2014). One promising therapeutic strategy is targeted therapy that involves blocking the BRAF kinase (about 50% of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It should also be taken into account that the oxidative stress that is generated by reactive oxygen species is closely associated with the induction of apoptosis. Previous studies have shown that these phenolic acids can disrupt redox homeostasis in the C32 cells, which can then trigger apoptosis [ 25 , 26 ]. Hence, high concentrations of polyphenols might exhibit pro-oxidative properties that could be used in the adjunctive treatment of cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be taken into account that the oxidative stress that is generated by reactive oxygen species is closely associated with the induction of apoptosis. Previous studies have shown that these phenolic acids can disrupt redox homeostasis in the C32 cells, which can then trigger apoptosis [ 25 , 26 ]. Hence, high concentrations of polyphenols might exhibit pro-oxidative properties that could be used in the adjunctive treatment of cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CGA and CA stock solutions were prepared in phosphate buffered saline (PBS, Sigma-Aldrich, St. Louis, MO, USA) and then diluted in the culture medium. The concentration of both acids was selected based on previous cytotoxicity studies, which had shown that a concentration of 1 mmol/L only reduced the viability of the C32 cells and had no significant effect on the viability of normal human dermal fibroblasts [ 25 , 26 ]. Moreover, the biological effects of a moderate-strength SMF do not exhibit cytotoxic properties as was indicated in previous reports [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AMF and static MF have not been analyzed in anticancer therapy yet. Only a few papers show the potential of magnetic field in the induction of cell death ( 231 , 232 ).…”
Section: Physical Methods and Their Mechanismsmentioning
confidence: 99%
“…The biological effects of weak magnetic treatments are mainly due to the affects the treatment has on the medium properties, physicochemical properties of cell membranes, structure of biological macromolecules, and free radicals. Magnetic fields can produce positive biological effects by influencing several aspects of media parameters, cell morphology structure, enzyme activity [118] , [119] and gene expression [130] , [131] , [132] , [133] .…”
Section: Physical Field Technology Characteristics and Mechanisms Of Actionmentioning
confidence: 99%